Bardo: An Intermediate State That Exited between Birth, Death and Rebirt - Kanjanaphitsarn, Supre (RUSAMILAE JOURNAL, 2022)
This article aims to study the body of knowledge about Bardo in The Tibetan Book of the Dead through documentary research. Compile the data and present the results of the study by descriptive method. The result of the study showed that the meaning of Bardo which used in the study of death is the state that existed between birth, death and rebirth. The content in the book describes the three main b ardos: 1) the painful bardo of dying covers from the first day of serious illness to the manifestation of clear flash 2) the luminous bardo of dhammata is the state in which the mind expressing the power of its original nature is manifested through sound, light and radiation, and ends with the manifestation of clear flash 3) the karmic bardo of becoming which ends when the soul of the departed is born in a new realm. There is also another important bardo is the bardo of life which starts from the first moment of fertilization until the first day of serious illness. This bardo is the best time for spiritual training to prepare for death. A study of Bardo's teachings pointed out that the significance of preparing for death, having an opportunity to enlighten even though a person is dead, and the relatives can help the deceased reach enlightenment or be born in a better realm.